The modified outer membrane protein Amuc_1100 of Akkermansia muciniphila improves chronic stress-induced anxiety and depression-like behavior in mice. Issue 20 (30th September 2022) - Cheng, Rongrong; Zhu, Haiyan; Sun, Yan; Hang, Tianrong; Zhang, Min
Abstract : Amuc_1100 Δ80 can improve anxiety and depression-like behavior of mice caused by chronic stress through the microbiota–gut–brain axis. Abstract : Akkermansia muciniphila is a next-generation probiotic. The interaction between outer membrane protein Amuc_1100 of A. muciniphila and toll-like receptor 2 (TLR2) in intestinal epithelial cells influences the level of intestinal 5-hydroxytryptamine (5-HT). Amuc_1100 Δ80 is a truncated form of Amuc_1100 lacking the first 80 N-terminal amino acids and has a higher affinity for TLR2 than the wild-type protein. Here, we report that Amuc_1100 Δ80 could significantly reduce anxiety and depression-like behavior of mice when they were exposed to chronic unpredictable mild stress (CUMS). The experimental results of the rat insulinoma cell line RIN-14B showed that Amuc_1100 Δ80 also induced a significantly higher upregulation of tryptophan hydroxylase 1 (Tph1), a rate-limiting enzyme of intestinal 5-HT synthesis. The imbalance of the gut microflora could be diminished when CUMS mice were fed with Amuc_1100 Δ80 . These results reveal that Amuc_1100 Δ80 could affect the 5-HT level and the downstream 5-HTR1A-CREB-BDNF signal pathway via interacting with TLR2 and by altering the gut microbial composition. In parallel, the downregulation exerted by Amuc_1100 Δ80 on the inflammation and hyperactivated HPA axis was closely related to the improvement of depression-like symptoms in CUMS mice. This study not only provides new insights into the antidepressant effect of A. muciniphila and its outer membrane protein Amuc_1100 but also identifies new potential targets and pathways in the gut for future research and the development of antidepressant drugs.